Aetiology, secondary prevention strategies and outcomes of ischaemic stroke despite oral anticoagulant therapy in patients with atrial fibrillation - Polymeris, Alexandros A.; Meinel, Thomas R.; Oehler, Hannah; Hoelscher, Kyra; Zietz, Annaelle; Scheitz, Jan F.; Nolte, Christian H.; Stretz, Christoph; Yaghi, Shadi; Stoll, Svenja; Wang, Ruihao; Haeusler, Karl Georg; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2022)
Objective To investigate the aetiology, subsequent preventive strategies and outcomes of stroke despite anticoagulation in patients with atrial fibrillation (AF).
CRIS-Team WoS Importer:2022-04-22